2017
DOI: 10.1002/cad.20192
|View full text |Cite
|
Sign up to set email alerts
|

Great Expectations: A Framework for Assessing and Understanding Key Factors Affecting Student Learning of Foundational Reading Skills

Abstract: This article addresses the evolution of the underlying theories of change in global education reform efforts between 1990 and 2015, informed by the shift in focus from access to quality and learning. We review recent data regarding how different types of donor interventions (i.e., structural or pedagogical) have contributed to improved reading outcomes and compare effect sizes over a series of intervention studies conducted from 2003 to 2015. Against this background, we present a framework for understanding ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…When considering why the impact of Tusome on learning outcomes over 1 year was somewhat larger than the gains experienced in the much smaller (but still substantial) pilot programs that preceded it , we note that the gains are both counterintuitive and outliers considering the literature on the typical impacts achieved when a reform moves from pilot to scale (e.g., Moore et al 2017). We posit that the relatively successful implementation of the first two areas of the core functions model allowed the program to focus on particular aspects of institutional capacity relating to these areas.…”
Section: Resultsmentioning
confidence: 90%
“…When considering why the impact of Tusome on learning outcomes over 1 year was somewhat larger than the gains experienced in the much smaller (but still substantial) pilot programs that preceded it , we note that the gains are both counterintuitive and outliers considering the literature on the typical impacts achieved when a reform moves from pilot to scale (e.g., Moore et al 2017). We posit that the relatively successful implementation of the first two areas of the core functions model allowed the program to focus on particular aspects of institutional capacity relating to these areas.…”
Section: Resultsmentioning
confidence: 90%
“…The entire time used to teach the reading curriculum focuses on teaching reading skills by using various reading strategies. Moore et al (2017) indicated that frequency, intensity, and fidelity influence the overall expected outcome of a reading program. These elements mentioned lead to a focused and targeted curriculum for struggling school-aged students.…”
Section: Explore Importance Of the Problemmentioning
confidence: 99%
“…Closing the reading gap among students with below-basic comprehension skills in schools throughout the United States is a challenge not only for schools and districts, but also for political and economic entities (Moore, Gove, & Tietjen, 2017). Schools face the challenge of educating students with an array of learning difficulties, socioeconomic backgrounds, and learning abilities.…”
Section: Introduce the Problemmentioning
confidence: 99%
See 2 more Smart Citations